2013
DOI: 10.1104/pp.113.233684
|View full text |Cite
|
Sign up to set email alerts
|

TAP46 Plays a Positive Role in the ABSCISIC ACID INSENSITIVE5-Regulated Gene Expression in Arabidopsis    

Abstract: TAP46 is a protein phosphatase2A (PP2A)-associated protein that regulates PP2A activity in Arabidopsis (Arabidopsis thaliana). To study how PP2A is involved in abscisic acid (ABA) signaling in plants, we studied the function of TAP46 in ABA-regulated seed maturation and seedling development. Expression of TAP46 coincides with the action of ABA in developing seeds and during seed germination, and the TAP46 transcript reaches to the highest level in mature seeds. Real-time polymerase chain reaction analysis indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 57 publications
1
63
0
1
Order By: Relevance
“…Future analyses will require investigations of SnRK2-type protein kinase activities in higher order pp2a mutants and in specific tissues and cell types and activity measurements of PP2A-type protein phosphatases after prolonged ABA treatments. Note that a 1-d ABA treatment drastically reduced PP2A-type phosphatase activity in germinating seeds (Hu et al, 2014).…”
Section: Pp2a-type Protein Phosphatases Function In Aba Responsesmentioning
confidence: 95%
See 1 more Smart Citation
“…Future analyses will require investigations of SnRK2-type protein kinase activities in higher order pp2a mutants and in specific tissues and cell types and activity measurements of PP2A-type protein phosphatases after prolonged ABA treatments. Note that a 1-d ABA treatment drastically reduced PP2A-type phosphatase activity in germinating seeds (Hu et al, 2014).…”
Section: Pp2a-type Protein Phosphatases Function In Aba Responsesmentioning
confidence: 95%
“…Differences between ABA responses in Ws and Col-0 may result from altered expression levels between natural accessions of Arabidopsis. For instance, PP2A-type protein phosphatase activity in Ws was 4-fold higher compared with that in Col-0 (Hu et al, 2014). Gene dosages of regulatory PP2AA subunits were discussed to be important for PP2A-type protein phosphatase function (DeLong, 2006).…”
Section: Pp2a-type Protein Phosphatases Function In Aba Responsesmentioning
confidence: 99%
“…These results showed that while the expression of ABI5 transcripts was not affected in amiR plants, ABI5-regulated gene expression was increased. Since PP2A negatively regulates ABI5 activity (Hu et al, 2014), these results could be interpreted to indicate that reduced PP2A activity in amiR plants may be responsible for the increased expression of ABI5 downstream genes.…”
Section: Pp2a Activity Was Reduced In Amir Plantsmentioning
confidence: 95%
“…The response of amiR plants to cantharidin, an inhibitor of PP2A and PP2A-related phosphatases such as PP6 (Li and Casida, 1992;Hu et al, 2014), was also analyzed. Four-day-old seedlings were transferred to MS plates that were not supplemented or were supplemented with 10 mM cantharidin, and plants were allowed to grow for an additional 4 d before the main root length was measured.…”
Section: Atptpa Is Essential For Plant Growth and Developmentmentioning
confidence: 99%
See 1 more Smart Citation